Epigenetic changes occur in placentas of spontaneous and recurrent miscarriages. (February 2022) - Meister, Sarah; Kellner, Isabel; Beyer, Susanne; Corradini, Stefanie; Schulz, Christian; Rogenhofer, Nina; Keilmann, Lucia; Kolben, Theresa Maria; Mahner, Sven; Kessler, Mirjana; Jeschke, Udo; Kolben, Thomas
Highlights: There are distinct profiles in epigenetic regulation in recurrent miscarriages (RM) compared to spontaneous miscarriages (SM). Histone modifications H3K4me3 and H3K9ac are overall reduced in placental tissue of SM. In recurrent miscarriages particularly H3K9ac is reduced. Histone modifications differ in the distinct compartments of the placental tissue. There might be an association to the downregulation of gene activation with the development of miscarriages. Abstract: Background: In contrast to genetic abnormalities which are well known to be responsible for around 50 % of human miscarriages, there is very few data about epigenetic alterations in spontaneous and recurrent miscarriages (SM, RM). The aim of this study was to analyze the histone modification marks H3K9ac and H3K4me3 in SM and RM. Methods: The abundance of histone modifications H3K4me3/H3K9ac was analyzed by western blot in frozen abortion material of SM and RM compared to a control group of legal pregnancy terminations. Further, to characterize placental tissue cells expressing H3K4me3/H3K9ac immunohistochemistry (IHC) and immunofluorescence was performed in 20 SM, 19 RM and 26 controls. Results: The western blot data showed a tendency to an overall reduction of H3K4me3/H3K9ac, in the placental tissue of particularly SM. Further we differentiated between syncytiotrophoblast, cytotrophoblast and decidual cells and found a significant decrease of H3K4me3 in SM in cytotrophoblast cells and syncytial stroma. In RM H3K4me3 was downregulated exclusively in the syncytiotrophoblast. H3K9ac was reduced in SM and RM in all evaluated compartments, except from the syncytiotrophoblast. Conclusion: Our study showed an overall reduced histone modification of H3K4me3 and H3K9ac in the placental tissue of SM. Concerning RM, particularly the reduction of H3K9ac was detected in the placental tissue, indicating that RM group has distinct profile in epigenetic regulation. Whether these histone modifications are part of a possible pathophysiologic cascade during SM and RM or are merely indicating a defective placentation, cannot be concluded from this study.